Effects of application of marine mud and manure on growth and yield of Capsicum annum L. on an Ultisol of Maluku - F Matulessy; T Wardiyati; S Syekhfani; N Aini (Journal of Degraded and Mining Lands Management, 2015)
Marine mud and manure are potential for improving ultisol conditions, especially soil acidity, CEC, base saturation, organic acid, soil structure, soil nutrient retention, aeration, soil humidity, water holding capacity, infiltration, and supply of phosphorus for plant growth and development. Two treatments, namely planting media with 200 t marine mud /ha + 30 t manure / ha, and 400 t marine mud /ha + 30 t manure / ha were able to increase pH from 4.6 to 5.6. A significant decrease of exchangeable Alsolubility of about 0.03 meq/100 g was found in M1O3; M2O1; M2O3 and M3O1 treatments. An increase of available phosphorus about 5.02 mg/kg was found at 200 t marine mud/ha + 30 t manure/ha treatment. There was a significant increase in plant height of about 62.42 cm in the media without marine mud and 30 t manure/ha. Application of 30 t manure/ hayielded plant with leaf size of about 9552 cm2 /plantand fresh fruit of about 9.81 t/ha.